(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2019)
In this article the outsourcing is defined as a modern and successful business model that enables the company to achieve competitive advantages. It was found out that this was not a new method, and it was originated in the West. It is used as a tool for lowering costs, improving service quality and production efficiency. The article analyses a certain number of modern scientific works of foreign scientists, as well as Ukrainian and Russian scientists, which are devoted to the problems of using outsourcing in different fields of economic agents’ activities. While analysing literary sources, the attention was paid to the investigation of aspects of enterprise management on the basis of logistic approaches in Ukraine. It is proved that one of the most effective methods for increasing the profitability of a business is the introduction of outsourcing in the logistics management. It is also determined that logistics outsourcing is purchasing of services for inventories management, goods transportation, their warehousing and all the other related with these processes business operations from a third party. The article deals with the activities of providers of logistic services considering the number of logistic functions, as well as the level of access to international and regional markets, and what is more they are divided into 5 levels of logistics service. The third party logistics is highlighted from the given classification, since the term 3PL is synonymous with the concept of outsourcing, which means the transfer of part or all of the logistics functions to a third party that is a provider of logistics services. Based on the research conducted by Armstrong & Associates in 2018, the global revenues and costs of 3PL operators were estimated. On the basis of the research results, it was defined that outsourcing has been tested and actively used in developed countries, and in recent decades it is being adapted to Ukraine. It has also been found that the combination of the effectiveness of the use of logistics tools and the trend of concentration of enterprises in the main activities provides opportunities for the development of the logistics outsourcing market.